Optimization of Pectin Extraction from Pomelo Peels (Citrus maxima) using Response Surface Methodology - Pagarra, Halifah; Hartati; Rachmawaty, Rachmawaty; Sahribulan, Sahribulan (Bionature, 2024)
Pectin is an essential polysaccharide that is usually found in the skin of various fruits and vegetables. It acts as a gelling agent and stabilizer in many food and pharmaceutical industries. This study focuses on the potential of grapefruit peel as a source of pectin. Pectin is isolated from hot grapefruit peel powder (albedo). The aim of this study was to extract pectin from grapefruit peel (albedo), and central composite design (CCD) together with the numerical optimization method of response surface methodology (RSM) was used to optimize the processing parameters, including temperature (60, 80 and 100 ° C), pH (1.5, 2.0 and 2.5 ) and time (60, 90 and 120 min) The findings show that the studied parameters have a major impact on the pectin yield. The resulting second-order polynomial model thoroughly explains the relationship between input and output variables and how the data is varied. The highest pectin yield was 28.45% at optimal conditions achieved: temperature: 100° C; pH: 1.5; and extraction time: 120 minutes. Temperature, pH, and extraction time have their own large impact on pectin yield which has a significant effect.